2020
DOI: 10.1101/2020.01.29.925784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

dnmt1function is required to maintain retinal stem cells within the ciliary marginal zone of the zebrafish eye

Abstract: The ciliary marginal zone (CMZ) of the zebrafish retina contains a population of actively proliferating resident stem cells, which generate retinal neurons throughout life. The maintenance methyltransferase, dnmt1, is expressed within the CMZ. Loss of dnmt1 function results in gene misregulation and cell death in a variety of developmental contexts, however, its role in retinal stem cell (RSC) maintenance is currently unknown. Here, we demonstrate that zebrafish dnmt1 s872 mutants possess severe defects in RSC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Further ISH experiment confirmed this result, that cdkn1a and tp53 were highly expressed in the OV of Dnmt1‐depleted animals. This finding broadly supports the previous work that the proliferation of retinal stem cell (RSC) is severely repressed and cell death is elevated after dnmt1 depletion 41 . However, this study demonstrated that knockdown of Dnmt1 increased the expression level of tp53 , while the study of Angileri et al 41 found that cell cycle inhibition was not in a tp53 ‐dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…Further ISH experiment confirmed this result, that cdkn1a and tp53 were highly expressed in the OV of Dnmt1‐depleted animals. This finding broadly supports the previous work that the proliferation of retinal stem cell (RSC) is severely repressed and cell death is elevated after dnmt1 depletion 41 . However, this study demonstrated that knockdown of Dnmt1 increased the expression level of tp53 , while the study of Angileri et al 41 found that cell cycle inhibition was not in a tp53 ‐dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, information has been published on the epigenetic status of cells in the zebrafish eye CMZ [ 70 ]. The study considers the DNA methylation in CMZ cells using Dnmt1, one of the DNA methyltransferase (Dnmt) enzymes that catalyzes the DNA methylation process [ 70 ].…”
Section: Eye Ciliary Zonementioning
confidence: 99%
“…Recently, information has been published on the epigenetic status of cells in the zebrafish eye CMZ [ 70 ]. The study considers the DNA methylation in CMZ cells using Dnmt1, one of the DNA methyltransferase (Dnmt) enzymes that catalyzes the DNA methylation process [ 70 ]. It was previously known that the loss of this enzyme results in genomic hypomethylation, and that Dnmt1 is capable of maintaining the function of progenitor cells in self-renewing somatic tissues [ 71 ].…”
Section: Eye Ciliary Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Retinal stem cells (RSCs) and progenitor cells (RPCs) are the adult multipotent cells which are capable of self-renewal and differentiation into almost all retinal cells (1). They were firstly discovered in lower vertebrates like urodele amphibians (2) and teleost fishes (3), which are located at a region called the ciliary marginal zone (CMZ) between neural retina and ciliary epithelium and present a high potential to proliferate and to generate retinal cells throughout life (4). Interestingly, it has been recognized that the stem cells resided in CMZ of frogs and fishes could be able to completely restore the retina after severe damages or retinal detachments (5).…”
Section: Introductionmentioning
confidence: 99%